Blood money: how criminals, militias, rebels, and warlords finance violence - Sankey, Margaret (Naval Institute Press, 2022)
"Blood Money analyzes the ways in which violent non-state actors find money for their operations and sustainment. Author Margaret Sankey highlights the mundane and everyday nature of these tactics. She points out the many ways VNSAs evade law enforcement, and she offers options for involving consumers and activists in exercising agency and choices in how they apply their money and where it goes. Blood Money also provides context for whole-of-government approaches to attacking underlying supports for illicit financing channels"--